The theme of the secondary image in the Leningrad psychological school - Golovinov, Evgenii Ivanovich; Gostev, Andrei Andreevich (Психолог, 2025)
The Leningrad (St. Petersburg) Psychological School is known for the fact that the center of interest of its founders and followers lie in complex human studies. In the context of the study of man at the Leningrad Psychological School (LPS), the theme of the secondary image, directly or in various aspects of the study of the image in psychology as such, can be traced back to the activities of V.M. Bekhterev. The term "secondary images" proposed by the LPS is used by its representatives as a general, systemic one for various kinds of figurative phenomena, and is associated with the level of representations of the subject. It is the secondary image that is central to the study of human behavior and psychoregulation in various situations, primarily related to the most cognitively problematic and value-significant for the subject. Secondary images determine communication with other people. Such communication is moving from the level of communication interaction to the level of education and the formation of social ideas, which is not always evaluated positively, and sometimes causes concern about the continuity of moral norms and values, the importance of direct communication and the preservation of traditions. The main conclusions of the study are the justification of the need for theoretical and practical development of the subject of secondary images in the general problem of human psyche research. Since the concept of a secondary image was born in the depths of the LPS, we consider it necessary to treat the history of its formation as a concept in the context of the interests of representatives of the Leningrad school. The latter is becoming increasingly relevant due to the digitalization of the space around a person, the transition from direct perception to the exchange of images provided by computer technologies used everywhere and the peculiarities of the modern information world. The contribution of the authors is determined by the analysis of the theme of the secondary image in a historically mediated sequential coverage of the stages of the formation of the problematic. The data of the theoretical study determine the importance and necessity of addressing the subject of the formation and transformation of a secondary image both in a general scientific context and from the perspective of practical use in psychotherapeutic work using altered states of consciousness.